The Existence of Learners in Language Learning - Ruwandi Ruwandi (IAIN Salatiga, 2008)
Caring of students in teaching-learning process should be one of the most important attentions of teachers. They should be the central body by which the measurement of success or failure is underpinned. Teachers will be considered successful when their students get scores above the passing grade. However, they must fail when the students get unsatisfactory achievements. Even though students’ success is the end of the aim of teaching-learning process but their involvement is not taken into account accordingly. To achieve such a goal, their internal potentials should be revitalized. The inner potentials include attitude, motivation, aptitude, and intelligence. The successful study can be achieved when the four internal potential are well managed. For that reason, teachers’ attention should be addressed to intensify the potentials to get the significant yield.Keywords: Care of; Internal Potentials; Attitude; Motivation; Aptitude;Intelligence